PEMANFAATAN KARTU PRAKERJA BAGI PEKERJA SEKTOR PARIWISATA YANG TERDAMPAK PANDEMI COVID-19 DI KUTA, BALI - Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This mixed-methods study analyzed consumption patterns among tourism sector workers before and during the pandemic in Kuta. The incentives received were primarily used for daily necessities, while respondents gained relevant skills training. The study concludes that the Pre-Employment Card Program benefits recipients in household consumption and skill development. Kuta, a prominent tourist destination in Bali, suffered significantly from the Covid-19 pandemic. Restrictions on tourist visits led to substantial income losses for local communities reliant on tourism. In response, the Indonesian government introduced the Pre-Employment Card Program to support affected workers, those laid off, and micro-enterprises experiencing declining sales. This study employed a mixed-methods approach, utilizing questionnaires to investigate differences in consumption patterns among Kuta's tourism sector workers before and during the pandemic. Analysis revealed a 45 percents decline in consumption among Pre-Employment Card recipients during the pandemic. Incentives received were primarily allocated for daily necessities. Respondents also benefited from skills training aligned with future needs. The study demonstrates a significant difference in consumption patterns pre- and post-pandemic. The Pre-Employment Card Program effectively supported household consumption and skill development among beneficiaries. Future implications highlight the program's benefits, emphasizing the need for sustained information dissemination and diverse training programs to enhance human resources.